IMPLEMENTATION OF THE STEM LEARNING TO IMPROVE THE CREATIVE THINKING SKILLS OF HIGH SCHOOL STUDENT IN THE NEWTON LAW OF GRAVITY MATERIAL - Jeni Pratika Surya; Abdurrahman; Ismu Wahyudi (JOURNAL OF KOMODO SCIENCE EDUCATION, 2018)
The purpose of the research is how to know the improvement of the ability to think creatively in class X high school students by using the STEM approach. The sample of this research is the student's class X science one SMAN 14 Bandarlampung school year 2017/2018. The research design used was One-Group-Pretest-Posttest. Creative students thinking ability data collected using the instrument’s ability creatively. The result showed that the value of Normalized Gain (N-Gain) around 0.57 with categories is being. As well as the value of the significance test Pairs Sample T-test of 0.000 meaning STEM learning approach to implementation is able to improve thinking ability creative students. In this study of the indicators most influential creative thinking towards the implementation of the approach STEM is flexible thinking skills seen indicators of assessment of pretest and posttest students who tested showed increased results significantly.